Vector Competence: What Has Zika Virus Taught Us? - Azar, Sasha R. (Viruses, 2019)
The unprecedented outbreak of Zika virus (ZIKV) infection in the Americas from 2015 to 2017 prompted the publication of a large body of vector competence data in a relatively short period of time. Although differences in vector competence as a result of disparities in mosquito populations and viral strains are to be expected, the limited competence of many populations of the urban mosquito vector, Aedes aegypti, from the Americas (when its susceptibility is viewed relative to other circulating/reemerging mosquito-borne viruses such as dengue (DENV), yellow fever (YFV), and chikungunya viruses (CHIKV)) has proven a paradox for the field. This has been further complicated by the lack of standardization in the methodologies utilized in laboratory vector competence experiments, precluding meta-analyses of this large data set. As the calls for the standardization of such studies continue to grow in number, it is critical to examine the elements of vector competence experimental design. Herein, we review the various techniques and considerations intrinsic to vector competence studies, with respect to contemporary findings for ZIKV, as well as historical findings for other arboviruses, and discuss potential avenues of standardization going forward.